A study of awareness and acceptance of islamic banking in Sri Aman / Azeni Sahat - Sahat, Azeni (2002)
The study made is mainly on the awareness and acceptance of Islamic banking in Sri Aman, with a special focus on Islamic product of Public Finance Berhad (PFB), Sri Aman branch. In addition, the study also touches briefly on growth of Islamic banking in PFB and the growth of Islamic banking in Malaysia as a whole. Government policies aim to promote growth and expansion of Islamic banking is also mentioned. The primary data of this study are gained from survey through questionnaires (as per appendix VI) which were distributed in late August 2002 and personal observation. Beside the primary data, information has also been collected through newspapers, magazines, annual report, speeches and some other reading material. From the response, some information has been collected which could be used to increase the share of Islamic banking particularly in Sri Aman.